Composite membrane as well as preparation method and application thereof

By adding core-shell particles formed by temperature-sensitive polymer particles and gold nanolayers to the moisture-permeable film, and using near-infrared light to form microscopic channels, the problem of moisture-permeable water suppression performance of the surface of the moisture-permeable film is solved, and the effect of rapid cleaning of condensate and improving the transfer rate of water molecules is achieved.

CN119752078APending Publication Date: 2025-04-04SHENZHEN SENIOR TECH MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411982315.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During use, the existing moisture-permeable films cause surface condensation due to reasons such as supersaturation of air humidity, which inhibits moisture-permeable performance and affects the fresh preservation and heat exchange effects.

Method used

Core-shell particles formed by temperature-sensitive polymer particles and gold nanolayers are distributed inside the base film and partially protrude on the surface to form protrusions. The core-shell particles are shrunk by near-infrared light to form microscopic channels, improve the water molecule transfer rate and clean the condensate.

Benefits of technology

It significantly improves the water molecule transfer rate and efficiency of the composite membrane, quickly and effectively cleans the condensate on the surface of the membrane, extends the service life and improves the fresh preservation and heat exchange effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752078A_ABST
    Figure CN119752078A_ABST
Patent Text Reader

Abstract

The invention provides a composite membrane as well as a preparation method and application thereof. The composite membrane comprises a base membrane and core-shell particles, wherein the core-shell particles are distributed in the base membrane and at least partially protrude out of the surface of the base membrane to form bulges; each core-shell particle comprises a temperature-sensitive polymer particle and a gold nano layer coated on the surface of the temperature-sensitive polymer particle. According to the invention, the core-shell particles formed by the thermo-sensitive polymer particles and the gold nanolayer are added into the base membrane, and part of the core-shell particles form bulges on the surface of the base membrane, so that condensed water on the surface of the composite membrane can be effectively cleaned, and the use effect of the composite membrane can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of moisture permeable membrane materials, and in particular relates to a composite membrane and a preparation method and application thereof. Background Art

[0002] The moisture permeable film has certain moisture permeability and can conduct moisture efficiently and controllably, and can then be used in scenarios such as preservation and heat exchange.

[0003] However, during use, condensation water often appears on the surface of the breathable membrane due to reasons such as oversaturated air humidity and temperature changes. The appearance of condensation water will significantly inhibit the breathability of the breathable membrane, causing water to be enriched on one side of the membrane surface. In the fresh-keeping scenario, condensation water will cause the surface of the food to become moist, accelerate the spoilage of the food, and may also affect the taste and appearance of the food. In addition, condensation water on the surface of the cling film will also cause the cling film to deform or be damaged, accelerate the aging of the cling film, shorten the service life of the cling film, and affect the use effect of the cling film. In the heat exchange scenario, the enrichment of condensation water on one side of the membrane causes the moisture permeability to be significantly reduced, and the efficiency of heat exchange through humidity is greatly reduced. Therefore, it is an urgent problem to be solved in this field to develop a composite membrane with a fast water molecule transfer rate, which can quickly and effectively clean up condensation water and ensure good air permeability of the material. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention aims to provide a composite membrane and its preparation method and application. The composite membrane solves the problem that the moisture permeable membrane in the prior art cannot quickly and effectively clean the condensed water formed on the surface of the membrane, resulting in a significant decrease in its use effect during application.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] In the first aspect, the present invention provides a composite film, which includes a base membrane and core-shell particles, wherein the core-shell particles are distributed inside the base membrane and at least partially protrude from the surface of the base membrane to form protrusions; the core-shell particles include thermosensitive polymer particles and a gold nanolayer coated on the surface of the thermosensitive polymer particles.

[0007] In the present invention, in the core-shell particles, the thermosensitive polymer particles are the core and the gold nanolayer is the shell; due to the plasma resonance effect, the surface of the gold nanolayer can produce a photothermal conversion phenomenon when irradiated with near-infrared light, generating a large amount of heat, and the generated heat will cause the thermosensitive polymer particles to respond to temperature stimulation, the core-shell particles will shrink, the size will be reduced, and microscopic channels will be formed between the core-shell particles and the base membrane, thereby significantly improving the water molecule transfer rate and water molecule transfer efficiency of the composite membrane; due to the difference in compatibility between the gold nanocoating layer and the base membrane, bulges are formed, which increases the contact area between the membrane and water molecules. Therefore, when there is condensation on the membrane surface due to reasons such as humidity oversaturation, When the condensed water is removed, the near-infrared light irradiation is ended, the thermosensitive polymer particles restore their original morphological characteristics, the microchannels shrink, and the water molecule transfer rate returns to the level before irradiation, thereby ensuring the good performance of the composite membrane; therefore, by adding core-shell particles formed by thermosensitive polymer particles and gold nanolayers to the base membrane and forming protrusions, the condensed water on the surface of the composite membrane can be quickly and effectively cleaned away, the moisture permeability is increased, and the use effect of the composite membrane is further improved.

[0008] In a second aspect, the present invention provides a method for preparing the composite film according to the first aspect, the preparation method comprising the following steps:

[0009] The raw materials of the base film are mixed with the core-shell particles to form a film, thereby obtaining the composite film.

[0010] In a third aspect, the present invention provides a use of the composite membrane as described in the first aspect in a cling film or a total heat exchange membrane.

[0011] In the present invention, the composite membrane is used for the total heat exchange membrane, which can improve the enthalpy efficiency of the total heat exchange membrane.

[0012] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] The composite membrane provided by the present invention adds core-shell particles formed by thermosensitive polymer particles and gold nanolayers into a base membrane, and the core-shell particles at least partially protrude from the surface of the base membrane to form protrusions. Under near-infrared light irradiation, the water molecule transfer rate and efficiency of the membrane are improved, so that condensed water on the membrane surface can be quickly and effectively cleaned and removed, thereby improving the use effect of the composite membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a schematic diagram of the structural changes of the core-shell particles of the present invention before and after near-infrared light irradiation;

[0016] Among them, 1-thermosensitive polymer particles; 2-gold nanolayer.

[0017] Figure 2 It is a schematic diagram of the structure of the composite film of the present invention before irradiation with near-infrared light;

[0018] Among them, 1-basement membrane; 2-core-shell particles.

[0019] Figure 3 is a schematic diagram of the structure of the composite film of the present invention after irradiation with near-infrared light;

[0020] Among them, 1-basement membrane; 2-core-shell particles. DETAILED DESCRIPTION

[0021] The technical scheme of the present invention is further described below by specific embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. In the embodiments of the present invention, if specific conditions are not specified, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0022] The present invention provides a composite film, which comprises a base film and core-shell particles. The core-shell particles are distributed inside the base film and at least partially protrude from the surface of the base film to form protrusions; the core-shell particles comprise thermosensitive polymer particles and a gold nanolayer coated on the surface of the thermosensitive polymer particles.

[0023] In the present invention, core-shell particles formed by thermosensitive polymer particles and gold nanolayers are added to the base film, and the core-shell particles at least partially protrude from the surface of the base film to form protrusions, so that condensed water on the surface of the composite membrane can be quickly and effectively cleaned and removed, thereby extending the service life of the moisture permeable membrane and improving the use effect.

[0024] It should be noted that the “surface” refers to the two surfaces with the largest area and arranged opposite to each other in a film or layer.

[0025] It should be noted that the base film in the present invention is a non-porous dense film.

[0026] Preferably, the number of protrusions in the composite film is 10 / 10 μm. 2 ~20 / 10μm2 , for example, 10 / 10 μm 2 , 11 / 10μm 2 , 12 / 10μm 2 , 13 / 10μm 2 , 14 / 10μm 2 , 15 / 10μm 2 , 16 / 10μm 2 , 17 / 10μm 2 , 18 / 10μm 2 , 19 / 10μm 2 , 20 / 10μm 2 Or a range consisting of any two of them.

[0027] The number of protrusions in the composite film is 10 / 10 μm. 2 ~20 / 10μm 2 Within this range, it is beneficial for the uniform dispersion of microscopic channels and their mutual penetration, further promoting the water molecule transfer rate and air permeability.

[0028] Preferably, the height of the protrusion is 20nm to 70nm, for example, it can be 20nm, 22nm, 25nm, 28nm, 30nm, 32nm, 35nm, 38nm, 40nm, 42nm, 45nm, 48nm, 50nm, 52nm, 55nm, 58nm, 60nm, 62nm, 65nm, 68nm, 70nm or a range consisting of any two thereof;

[0029] Preferably, the diameter of the protrusion is 120nm to 180nm, for example, it can be 120nm, 122nm, 125nm, 128nm, 130nm, 132nm, 135nm, 138nm, 140nm, 142nm, 145nm, 148nm, 150nm, 152nm, 155nm, 158nm, 160nm, 162nm, 165nm, 168nm, 170nm, 172nm, 175nm, 178nm, 180nm or a range consisting of any two of them.

[0030] The composite membrane controls the height of the protrusions to be within the range of 20nm to 70nm and the diameter to be within the range of 120nm to 180nm, which is beneficial to further ensure that the membrane has a suitable contact area with water molecules and further improve the water molecule transfer rate and air permeability.

[0031] In the present invention, the height of the protrusions on the surface of the composite film can be obtained by testing with a confocal microscope or a scanning electron microscope. For example, a scanning electron microscope SEM (Zeiss, model Gemini360) can be used to observe the cross-section of the composite film, and the protrusion heights within an observation field of view with a length of 1 μm can be randomly selected, and the arithmetic average is taken as the protrusion height.

[0032] In the present invention, the diameter and number of the protrusions on the surface of the composite film can be obtained by scanning electron microscopy (SEM) testing. For example, a scanning electron microscope SEM (Zeiss, model Gemini360) can be used to count the number of protrusions within a 5μm×5μm area field of view and measure the protrusion diameter under 10K magnification conditions, and then calculate the number of protrusions per unit area (1μm 2 ) is the number of protrusions per unit area, and the arithmetic average of the protrusion diameters in the field of view is the protrusion diameter.

[0033] Preferably, the molecular structure of the thermosensitive polymer particles contains amino groups.

[0034] In the present invention, the gold nanolayer can coordinate with the amino group in the thermosensitive polymer particles, and the gold nanolayer and the thermosensitive polymer can be connected to each other by sharing lone pair electrons to form a coordinated covalent bond or an ionic bond formed by electrostatic attraction, forming an Au-N electron donor-electron acceptor, so that the core-shell particle structure is stable, and at the same time, the core-shell particles can be evenly distributed in the base film. During use, the composite film continuously absorbs and transfers water molecules, and the amino groups interact and combine with the water molecules, so that the polymer chains of the core-shell particles are fully extended, resulting in substantially no gap between the core-shell particles and the base film; when irradiated with near-infrared light, the core-shell particles shrink, the size decreases, and a gap is formed between the core-shell particles and the base film, which is beneficial to promoting the transfer rate and air permeability of water molecules.

[0035] Preferably, the thermosensitive polymer particles include at least one of poly (N,N-dimethylaminoethyl methacrylate) (PDMAEMA), poly ((N,N-diethylaminoethyl methacrylate)) (PDEAEMA), and derivatives thereof.

[0036] The derivative refers to a compound that can be obtained by introducing a new functional group into the molecular structure of the thermosensitive polymer particle or changing its structure through chemical modification according to actual use requirements. For example, the derivative of PDMAEMA can be PDMAEMA-N3, β-cyclodextrin-polymethacrylate N,N-dimethylaminoethyl ester (β-CD-PDMAEMA), a block copolymer of polymethacrylate N,N-dimethylaminoethyl ester (PDMAEMA) and polycaprolactone (PCL) (PCL-b-PDMAEMA), a block copolymer of polylactic acid (PLA) and PDMAEMA (PCL-b-PDMAEMA), a block copolymer of polylactic acid (PLA) and PDMAEMA (PCL-b-PDMAEMA), a block copolymer of polylactic acid (PLA) and polycaprolactone (PCL) ... The derivatives of PDEAEMA can be polyethylene glycol (PEG) modified PDEAEMA, polylactic acid (PLA) and PDEAEMA to form a block copolymer (PLA-b-PDEAEMA), hydroxyethyl cellulose (HEC) modified grafted poly [methacrylic acid (N,N-diethylaminoethyl)] (PDEAEMA) to form a HEC-PDMAEMA grafted modified polymer, etc. The derivatives of PDEAEMA can be polyethylene glycol (PEG) modified PDEAEMA, polylactic acid (PLA) and PDEAEMA to form a block copolymer (PLA-b-PDEAEMA), hydroxyethyl cellulose (HEC) modified grafted PDEAEMA to form a HEC-PDEAEMA grafted polymer, etc.

[0037] Preferably, the average particle size of the thermosensitive polymer particles is 200nm to 300nm, for example, it can be 200nm, 205nm, 210nm, 215nm, 220nm, 225nm, 230nm, 235nm, 240nm, 245nm, 250nm, 255nm, 260nm, 265nm, 270nm, 275nm, 280nm, 285nm, 290nm, 295nm, 300nm or a range consisting of any two of them.

[0038] In the present invention, the average particle size of the thermosensitive polymer particles is the particle size of the core in the core-shell particles; by selecting a suitable average particle size of the thermosensitive polymer particles, it is beneficial to ultimately form core-shell particles with stable structure and good particle size uniformity, which is further beneficial to improving the transfer effect of water molecules.

[0039] In the present invention, the average particle size of the thermosensitive polymer particles and the gold nanoparticles can be obtained by transmission electron microscopy (TEM) observation and testing. For example, a transmission electron microscope (TEM) (Hitachi High-Technologies, model H-7650) can be used to take 10 photos at 100,000 to 200,000 times. The particle size of 50 polymer particles in the core-shell structure or the particle size of the gold nanoparticles can be measured on the photographed screen using the software attached to the TEM, and the particle size of the thermosensitive polymer particles or the particle size of the gold nanoparticles can be calculated as the arithmetic average thereof. The particle size distribution of the raw material can also be determined by particle size distribution, and the particle size corresponding to Dv50 is the average particle size.

[0040] Preferably, the thickness of the gold nanolayer is 40nm to 200nm, for example, it can be 40nm, 42nm, 44nm, 46nm, 48nm, 50nm, 52nm, 54nm, 56nm, 58nm, 60nm, 62nm, 64nm, 66nm, 68nm, 70nm, 72nm, 74nm, 76nm, 78nm, 80nm, 82nm, 84nm, 86nm, 88nm, 90nm, 92nm, 94nm, 96nm, 98nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm or a range consisting of any two of them.

[0041] By controlling the thickness of the gold nanolayer, the gold nanoparticle layer can be more stably combined with the thermosensitive polymer, which is further conducive to the formation of good microscopic channels between the core-shell particles and the basement membrane body, thereby obtaining a better water molecule transfer effect.

[0042] In the present invention, the thickness of the gold nanolayer can be obtained by transmission electron microscopy (TEM) testing.

[0043] Preferably, the gold nanolayer includes at least one of gold nanoparticles and one-dimensional gold nanomaterials.

[0044] In the present invention, the one-dimensional gold nanomaterial can be classified into at least one of gold nanorods, gold nanotubes, and gold nanowires according to their morphology.

[0045] Preferably, the gold nanoparticles or one-dimensional gold nanomaterials satisfy at least one of the following conditions:

[0046] a), the average particle size of the gold nanoparticles is 50nm to 150nm; for example, it can be 50nm, 52nm, 55nm, 58nm, 60nm, 62nm, 65nm, 68nm, 70nm, 72nm, 75nm, 78nm, 80nm, 82nm, 85nm, 88nm, 90nm, 92nm, 95nm, 98nm, 100nm, 102nm, 105nm, 108nm, 110nm, 112nm, 115nm, 118nm, 120nm, 122nm, 125nm, 128nm, 130nm, 132nm, 135nm, 138nm, 140nm, 142nm, 145nm, 148nm, 150nm or a range consisting of any two of them.

[0047] b) The aspect ratio of the one-dimensional gold nanomaterial is 5 to 20; for example, it can be 5, 5.2, 5.5, 5.8, 6, 6.2, 6.5, 6.8, 7, 7.2, 7.5, 7.8, 8, 8.2, 8.5, 8.8, 9, 9.2, 9.5, 9.8, 10, 10.2, 10.5, 10.8, 11, 11.2, 11.5, 11.8, 12, 12.2, 12.5, 19.2, 19.5, 19.8, 20, or a range consisting of any two of these.

[0048] c) The length of the one-dimensional gold nanomaterial is 20nm to 125nm, for example, it can be 20nm, 22nm, 24nm, 26nm, 28nm, 30nm, 32nm, 34nm, 36nm, 38nm, 40nm, 42nm, 44nm, 46nm, 48nm, 50nm, 52nm, 54nm, 56nm, 58nm, 60nm, 62nm, 64nm, 66nm, 68nm, 70nm, 72nm, 74nm, 76nm, 78nm, 80nm, 82nm, 84nm, 86nm, 88nm, 90nm, 92nm, 94nm, 96nm The diameter of the one-dimensional gold nanomaterial is 5nm to 25nm, for example, it can be 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm, 24nm, 25nm or a range consisting of any two of them.

[0049] By selecting the size of gold nanoparticles and one-dimensional gold nanomaterials, it is beneficial to stably and evenly coat the surface of the thermosensitive polymer particles to form a shell layer with more uniform thickness, thereby further improving the moisture permeability change rate and obtaining a better water molecule transfer effect.

[0050] In the present invention, the length and diameter of the one-dimensional gold nanomaterial can be observed by a scanning electron microscope (SEM) or a transmission electron microscope (TEM). For example, a transmission electron microscope (TEM) (Hitachi High-Technologies, model H-7650) can be used to take 10 photos at 100,000 to 200,000 times, and the diameter and length of 50 one-dimensional nanomaterials can be measured on the photographed screen by software attached to the TEM, and the length and diameter of the one-dimensional gold nanomaterial can be obtained as the arithmetic mean.

[0051] In the present invention, the diameter of the core-shell particles is 200nm to 600nm, for example, it can be 200nm, 205nm, 210nm, 215nm, 220nm, 225nm, 230nm, 235nm, 240nm, 245nm, 250nm, 255nm, 260nm, 265nm, 270nm, 275nm, 280nm, 285nm, 290nm, 295nm, 300nm, 310nm, 320nm, 340nm, 360nm, 380nm, 400nm, 430nm, 450nm, 480nm, 500nm, 520nm, 550, 580nm, 600nm or the range composed of any two of them.

[0052] By controlling the diameter of the core-shell particles within the range of 200 nm to 600 nm, the nanoparticles can be further stably and evenly dispersed in the polymer film body, and suitable protrusions and better microscopic channels can be further formed.

[0053] Preferably, the thickness of the composite film is 0.6 μm to 3 μm, for example, it can be 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm or a range consisting of any two of them.

[0054] The composite membrane has a thickness of 0.6 μm to 3 μm, which is conducive to suitable mechanical strength and a suitable water molecule transmission path.

[0055] The present invention also provides a method for preparing the composite membrane, which comprises the following steps: mixing raw materials of the base membrane with core-shell particles to form a membrane, thereby obtaining the composite membrane.

[0056] Preferably, the mass ratio of the raw materials of the base film to the core-shell particles is (4-10):1, wherein the specific values ​​in (4-10) can be, for example, 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.6, 5.8, 6, 6.2, 6.4, 6.6, 6.8, 7, 7.2, 7.4, 7.6, 7.8, 8, 8.2, 8.4, 8.6, 8.8, 9, 9.2, 9.4, 9.6, 9.8, 10 or a range consisting of any two of them.

[0057] By controlling the mass ratio of the raw materials of the base membrane to the core-shell particles to (4-10):1, the core-shell particles are more evenly distributed in the base membrane without agglomeration, thereby forming better protrusions and better microscopic channels.

[0058] Preferably, the raw material of the base film comprises a polymer.

[0059] Preferably, the polymer includes at least one of polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyethylene oxide (PEO), polymethacrylic acid (PMAA), polyacrylic acid (PAA), hydroxypropyl methylcellulose (HPMC) or hyaluronic acid (HA).

[0060] Based on the consideration of film density, the weight average molecular weight of the polymer is 40KDa~100KDa (i.e. 40000Da~100000Da), for example, it can be 40KDa, 45KDa, 50KDa, 55KDa, 60KDa, 65KDa, 70KDa, 75KDa, 80KDa, 85KDa, 90KDa, 95KDa, 100KDa or the range composed of any two of them; the weight average molecular weight of the polymer can be measured by GPC.

[0061] It should be noted that the raw materials of the above-mentioned base film can be mixed with additives such as phenol-based, phosphorus-based or sulfur-based antioxidants, metal soaps such as calcium stearate or zinc stearate, ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, coloring pigments, etc. as needed.

[0062] Preferably, the method for preparing the core-shell particles comprises: mixing the thermosensitive polymer particles, the material of the gold nanolayer and a solvent, and drying to obtain the core-shell particles.

[0063] Preferably, the temperature at which the thermosensitive polymer particles, the material of the gold nanolayer and the solvent are mixed is greater than the critical phase transition temperature (LCST temperature) of the thermosensitive polymer particles.

[0064] Preferably, the mixing time of the thermosensitive polymer particles, the gold nanolayer material and the solvent is 0.5 h to 2 h, for example, 0.5 h, 0.6 h, 0.8 h, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h or any two thereof.

[0065] By controlling the mixing temperature to be higher than the LCST temperature of the thermosensitive polymer particles, it is beneficial to achieve more uniform coating of the gold nanolayer material in the core-shell structure.

[0066] Controlling the mixing time to 0.5 h to 2 h can help further improve the structural stability of the core-shell particles.

[0067] Preferably, the preparation method of the thermosensitive polymer particles can be exemplified by dialysis self-assembly technology or microfluidics.

[0068] Specifically, the dialysis self-assembly technology can be to dissolve the thermosensitive polymer in an organic solvent, then put the solution into a dialysis bag, put the dialysis bag into deionized water, and perform dialysis. The retention weight average molecular weight of the dialysis bag is 500Da to 1000Da. After dialysis for 12h to 24h, freeze-drying is performed to obtain the thermosensitive polymer particles.

[0069] Specifically, the microfluidic technology can be to dissolve the thermosensitive polymer in an organic solvent, inject the thermosensitive polymer solution into deionized water at a rotation speed of 100rpm to 1000rpm at a certain flow rate to obtain a thermosensitive particle dispersion, and then freeze-dry the dispersion to obtain thermosensitive polymer particles.

[0070] Preferably, the temperature at which the raw materials of the base film are mixed with the core-shell particles is lower than the critical phase transition temperature of the thermosensitive polymer particles.

[0071] By controlling the mixing temperature to be lower than the LCST temperature of the thermosensitive polymer particles, the structural compactness of the composite film is facilitated.

[0072] The film forming method is not particularly limited in the present invention, and the film can be prepared using an existing film forming method.

[0073] Preferably, the film forming method may be a coating method or a casting method.

[0074] In the present invention, the coating method or the casting method is performed on the surface of a substrate, and the substrate includes a polyethylene terephthalate (PET) release film or glass.

[0075] Preferably, the film forming process further includes drying and peeling steps.

[0076] As a preferred technical solution of the present invention, the method for preparing the composite film comprises:

[0077] (1) Thermosensitive polymer particles are prepared by microfluidics or dialysis self-assembly technology, and after freeze-drying, they are dispersed in a solvent (the solvent includes water) with a temperature higher than the LCST temperature of the thermosensitive polymer. Then, gold nanolayer materials are added thereto, mixed for 0.5 h to 2 h, and then freeze-dried to obtain core-shell particles with the core being the thermosensitive polymer particles and the shell being the gold nanolayer.

[0078] (2) Under the condition of a temperature lower than the LCST temperature of the thermosensitive polymer particles, the core-shell particles and the raw materials of the base film are mixed, and then coated or cast into a film, dried, and peeled off to obtain the composite film; the film formation is carried out on a PET release film or glass.

[0079] In a third aspect, the present invention provides a use of the composite membrane as described in the first aspect in a cling film or a total heat exchange membrane.

[0080] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0081] The technical solution provided by the present invention will be clearly and completely described below in conjunction with the accompanying drawings, embodiments and comparative examples. Obviously, the specific implementation methods described are only part of the implementation methods of the present invention, rather than all the implementation methods.

[0082] The materials used in the present invention can be purchased from the market or prepared by conventional methods; unless otherwise specified, the materials used in the present invention are as follows:

[0083] Materials of the base film: polyvinyl alcohol (PVA): weight average molecular weight of 75 KDa, purchased from Anhui Wanwei; polymethacrylic acid (PMAA): weight average molecular weight of 120 KDa, purchased from Aladdin Reagent; hyaluronic acid (HA): weight average molecular weight of 200 KDa, purchased from Shandong Freda; polyethylene oxide (PEO): weight average molecular weight of 100 KDa, purchased from Aladdin Reagent.

[0084] Thermosensitive polymers: poly (N,N-dimethylaminoethyl methacrylate) (PDMAEMA): weight average molecular weight of 5 KDa, purchased from Hangzhou Xinqiao Biotechnology Co., Ltd.; poly (methacrylate (N,N-diethylaminoethyl)) (PDEAEMA): weight average molecular weight of 10 KDa, purchased from Aladdin Reagents; poly (N-isopropylacrylamide) (PNIPAM): weight average molecular weight of 40 KDa, purchased from Merck Reagents.

[0085] Materials for the gold nanolayer were purchased from Jiangsu Xianfeng Nanotechnology.

[0086] Example 1

[0087] The present embodiment provides a composite film, the thickness of the composite film is 2 μm, comprising a PVA base film and core-shell particles distributed inside and on the surface of the PVA base film; wherein some of the core-shell particles form protrusions on the surface of the composite film, the height of the protrusions is 50 nm, the diameter of the protrusion structure is 150 nm, and the number of the protrusion structures is 15 / 10 μm 2 .

[0088] The core-shell particles have a diameter of 410 nm and include PDMAEMA particles and a gold nanolayer coated on the surface of the PDMAEMA particles; the average particle size of the PDMAEMA particles is 250 nm, and the thickness of the gold nanolayer is 80 nm; the material of the gold nanolayer includes gold nanoparticles with an average particle size of 70 nm.

[0089] This embodiment provides a method for preparing the composite film, which specifically comprises the following steps:

[0090] (1) PDMAEMA particles of a specific particle size are prepared by dialysis self-assembly technology, and after freeze-drying at -80°C, the PDMAEMA particles are dispersed in deionized water (the mass of deionized water is 50 times that of the PDMAEMA particles) at 40°C (the LCST temperature of the PDMAEMA particles is 35°C), and then gold nanoparticles are added thereto, mixed for 1 hour, and freeze-dried at -80°C to obtain the core-shell particles; the specific process of the dialysis self-assembly technology is: PDMAEMA polymer is dissolved in DMSO to form a solution with a concentration of 1 g / mL, and then the solution is loaded into a dialysis bag, and the dialysis bag is placed in deionized water for dialysis, and the dialysis bag has a retention weight average molecular weight of 1000Da. After dialysis for 24 hours, the PDMAEMA particles are freeze-dried to obtain.

[0091] (2) At 26° C., the core-shell particles obtained in step (1) and PVA (the mass ratio of PVA to core-shell particles is 7:1) are mixed with deionized water (the mass of deionized water is 17 times the total mass of the core-shell particles and PVA), and then coated on the glass surface, dried at 60° C., and peeled off to obtain the composite film.

[0092] In the present invention, the structural schematic diagram of the core-shell particles after near-infrared light irradiation is as follows Figure 1 As shown in FIG. 1 , the core-shell particles shrink and their size decreases after being irradiated with near-infrared light. The schematic diagram of the structure of the composite film before and after irradiation with near-infrared light is shown in FIG. Figure 2 (before irradiation) and Figure 3 As shown in (after irradiation), after irradiation with near-infrared light, the core-shell particles shrink and become smaller in size, forming microscopic channels between the basement membrane and the core-shell particles.

[0093] Example 2

[0094] The present embodiment provides a composite film, the thickness of the composite film is 1 μm, including a PMAA base film and core-shell particles distributed inside and on the surface of the PMAA base film; wherein some of the core-shell particles form protrusions on the surface of the composite film, the height of the protrusions is 60 nm, the diameter of the protrusion structure is 155 nm, and the number of the protrusion structures is 19 / 10 μm 2 .

[0095] The core-shell particles have a diameter of 520 nm and include PDEAEMA particles and a gold nanolayer coated on the surface of the PDEAEMA particles; the average particle size of the PDEAEMA particles is 220 nm, and the thickness of the gold nanolayer is 150 nm; the material of the gold nanolayer includes gold nanoparticles with an average particle size of 140 nm.

[0096] This embodiment provides a method for preparing the composite film, which specifically comprises the following steps:

[0097] (1) PDEAEMA particles of a specific particle size are prepared by microfluidic technology, and after freeze-drying at -80°C, the PDEAEMA particles are dispersed in deionized water (the mass of deionized water is 50 times that of the PDEAEMA particles) at 50°C (the LCST temperature of the PDEAEMA particles is 37°C), and then gold nanoparticles are added thereto, mixed for 1 hour, and freeze-dried at -80°C to obtain the core-shell particles; the specific process of the microfluidic technology is: PDEAEMA is dissolved in DMSO to form a polymer solution with a concentration of 1 g / mL, and the polymer solution is injected into deionized water at a rotation speed of 500 rpm at a flow rate of 5 mL / min to obtain a dispersion, and then the dispersion is freeze-dried to obtain the PDEAEMA particles.

[0098] (2) At 26° C., the core-shell particles obtained in step (1) and PMAA (the mass ratio of PMAA to core-shell particles is 4.5:1) are mixed with deionized water (the mass of deionized water is 17 times the total mass of the core-shell particles and PMAA), and then coated on the glass surface, dried at 60° C., and peeled off to obtain the composite film.

[0099] Example 3

[0100] The present embodiment provides a composite membrane, the thickness of the composite membrane is 3 μm, including a HA base membrane and core-shell particles distributed inside and on the surface of the HA base membrane; wherein some core-shell particles form protrusions on the surface of the composite membrane, the height of the protrusions is 65 nm, the diameter of the protrusion structure is 170 nm, and the number of the protrusion structures is 12 / 10 μm 2 .

[0101] The core-shell particles have a diameter of 470 nm and include PDMAEMA particles and a gold nanolayer coated on the surface of the PDMAEMA particles; the average particle size of the PDMAEMA particles is 280 nm, and the thickness of the gold nanolayer is 95 nm; the material of the gold nanolayer includes gold nanorods (aspect ratio of 6) with a length of 78 nm and a diameter of 13 nm.

[0102] The method for preparing the composite membrane is different from that of Example 1 only in that the mass ratio of HA to core-shell particles is 9:1, and other step parameters are the same as those of Example 1.

[0103] Example 4

[0104] The present embodiment provides a composite membrane, the thickness of the composite membrane is 2 μm, comprising a PEO-based membrane and core-shell particles distributed inside and on the surface of the PEO-based membrane; wherein some of the core-shell particles form protrusions on the surface of the composite membrane, the height of the protrusions is 70 nm, the diameter of the protrusion structure is 175 nm, and the number of the protrusion structures is 14 / 10 μm 2 .

[0105] The core-shell particles have a diameter of 520 nm and include PDMAEMA particles and a gold nanolayer coated on the surface of the PDMAEMA particles; the average particle size of the PDMAEMA particles is 260 nm, and the thickness of the gold nanolayer is 130 nm; the material of the gold nanolayer includes a gold nanorod (aspect ratio of 20) with a length of 100 nm and a diameter of 5 nm. The preparation method of the composite membrane is different from that of Example 1 only in that the mass ratio of the PEO to the core-shell particles is 5:1, and the other step parameters are the same as those of Example 1.

[0106] Example 5

[0107] This embodiment provides a composite film, which is different from the embodiment 1 only in that the height of the protrusion is 35nm, the diameter of the protrusion structure is 125nm, and the number of the protrusion structure is 16 / 10μm. 2 The diameter of the core-shell particles is 310 nm, and the average particle size of the PDMAEMA particles is 150 nm; other components, dosages and process parameters are the same as those in Example 1.

[0108] Example 6

[0109] This embodiment provides a composite film, which is different from the embodiment 1 only in that the height of the protrusion is 65nm, the diameter of the protrusion structure is 180nm, and the number of the protrusion structure is 13 / 10μm. 2The diameter of the core-shell particles is 510 nm, and the average particle size of the PDMAEMA particles is 350 nm; other components, dosages and process parameters are the same as those in Example 1.

[0110] Example 7

[0111] This embodiment provides a composite film, which is different from the embodiment 1 only in that the height of the protrusion is 45nm, the diameter of the protrusion structure is 140nm, and the number of the protrusion structure is 15 / 10μm. 2 The diameter of the core-shell particles is 320 nm, the thickness of the gold nanolayer is 35 nm, and the average particle size of the gold nanoparticles is 30 nm; other components, dosages and process parameters are the same as those in Example 1.

[0112] Example 8

[0113] This embodiment provides a composite film, which is different from the embodiment 1 only in that the height of the protrusion is 75nm, the diameter of the protrusion structure is 185nm, and the number of the protrusion structure is 15 / 10μm. 2 The diameter of the core-shell particles is 640 nm, the average particle size of the PDMAEMA particles is 300 nm, the thickness of the gold nanolayer is 170 nm, and the average particle size of the gold nanoparticles is 150 nm; the other components, dosages and process parameters are the same as those in Example 1.

[0114] Example 9

[0115] This embodiment provides a composite film, which is different from the embodiment 1 only in that the height of the protrusion is 45nm, the diameter of the protrusion structure is 150nm, and the number of the protrusion structure is 15 / 10μm. 2 ; The diameter of the core-shell particles is 390nm, the thickness of the gold nanolayer is 70nm, and the average particle size of the gold nanoparticles is 40nm; the other components, dosages and process parameters are the same as those in Example 1.

[0116] Example 10

[0117] This embodiment provides a composite film, which is different from the embodiment 1 only in that the height of the protrusion is 75nm, the diameter of the protrusion structure is 185nm, and the number of the protrusion structure is 15 / 10μm. 2 ; The diameter of the core-shell particles is 690nm, the thickness of the gold nanolayer is 220nm, and the average particle size of the gold nanoparticles is 180nm; the other components, dosages and process parameters are the same as those in Example 1.

[0118] Embodiment 11

[0119] This embodiment provides a composite film, which is different from the embodiment 3 only in that the length of the gold nanorods is 80 nm, the diameter is 25 nm, and the aspect ratio is 3.2; the other components, amounts and process parameters are the same as those in the embodiment 3.

[0120] Example 12

[0121] This embodiment provides a composite film, which is different from the embodiment 3 only in that the length of the gold nanorods is 300 nm, the diameter is 20 nm, and the aspect ratio is 15; the other components, amounts and process parameters are the same as those in the embodiment 3.

[0122] Example 13

[0123] This embodiment provides a composite film, which is different from the embodiment 1 only in that the height of the protrusion is 50nm, the diameter of the protrusion structure is 150nm, and the number of the protrusion structure is 30 / 10μm. 2 In the preparation method, the mass of the core-shell particles is adjusted so that the mass ratio of PVA to the core-shell particles is 2:1, and the other components, amounts and process parameters are the same as those in Example 1.

[0124] Embodiment 14

[0125] This embodiment provides a composite film, which is different from the embodiment 1 only in that the height of the protrusion is 50nm, the diameter of the protrusion structure is 150nm, and the number of the protrusion structure is 7 / 10μm. 2 In the preparation method, the mass of the core-shell particles is adjusted so that the mass ratio of PVA to the core-shell particles is 12:1, and the other components, amounts and process parameters are the same as those in Example 1.

[0126] Embodiment 15

[0127] This embodiment provides a composite membrane, which differs from the embodiment 1 only in that the PDMAEMA particles are replaced with PNIPAM particles of equal mass and average particle size, the height of the protrusion is 50nm, the diameter of the protrusion structure is 150nm, and the number of the protrusion structure is 15 / 10μm. 2 ; Other components, dosages and process parameters are the same as those in Example 1.

[0128] Comparative Example 1

[0129] This comparative example provides a composite membrane, which differs from Example 1 only in that the core-shell particles are replaced with PDMAEMA particles of equal mass, the composite membrane does not have a convex structure, and the other components, amounts and process parameters are the same as those in Example 1.

[0130] Comparative Example 2

[0131] This comparative example provides a membrane material, which is different from Example 1 only in that the membrane material does not contain core-shell particles, the composite membrane does not have a protruding structure, and other components, amounts and process parameters are the same as those in Example 1.

[0132] Performance Testing

[0133] The following performance tests were performed on the composite membranes provided in Examples 1 to 15, Comparative Example 1, and the membrane materials provided in Comparative Example 2.

[0134] (1) Water molecule transfer rate: Referring to standard GB / T 1037-2021, the water molecule transfer rate of the composite film before irradiation with near-infrared light (wavelength of 780 nm to 1100 nm) and after continuous irradiation for 30 min was tested at 38°C and 90% relative humidity; and the change rate of water molecule transfer rate was calculated; wherein, the change rate of water molecule transfer rate = (water molecule transfer rate after continuous irradiation for 30 min - water molecule transfer rate before irradiation) / water molecule transfer rate before irradiation × 100%.

[0135] (2) Air permeability: Referring to the standard GB / T 36363-2018, the air permeability of the composite film was tested before and after near-infrared light irradiation; and the air permeability change rate was calculated; where the air permeability change rate = (air permeability after continuous irradiation for 30 min - air permeability before irradiation) / air permeability before irradiation × 100%.

[0136] The composite membrane provided in Comparative Example 1 was tested for its water molecule transmission rate and air permeability before and after treatment at 38° C. and 90% relative humidity.

[0137] The specific test results are shown in Table 1:

[0138] Table 1

[0139]

[0140] As can be seen from Table 1, the composite membrane provided by the present invention, by adding core-shell particles formed by thermosensitive polymer particles and gold nanolayers into the base membrane, and the core-shell particles at least partially protrude from the surface of the base membrane to form protrusions, is beneficial to improving the water molecule transfer rate and efficiency of the membrane under near-infrared light irradiation, so that the condensed water on the membrane surface can be quickly and effectively cleaned and removed, avoiding the influence of the condensed water on the performance of the composite membrane, and improving the use effect of the composite membrane.

[0141] It can be seen from Comparative Examples 1 and 2 that when the core-shell particles are replaced with thermosensitive polymer particles or there are no core-shell particles in the base membrane, the water molecule transfer rate is not improved after irradiation, the moisture permeability is poor, the water molecule transfer efficiency is low, which is not conducive to the removal of condensed water and affects the use effect of the composite membrane.

[0142] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite film, characterized in that The composite membrane comprises a base membrane and core-shell particles, wherein the core-shell particles are distributed inside the base membrane and at least partially protrude from the surface of the base membrane to form protrusions; The core-shell particles include thermosensitive polymer particles and a gold nanolayer coated on the surface of the thermosensitive polymer particles.

2. The composite membrane according to claim 1, characterized in that The number of protrusions in the composite film is 10 / 10 μm 2 ~20 / 10μm 2 ; Preferably, the height of the protrusion is 20nm to 70nm; Preferably, the diameter of the protrusion is 120nm-180nm.

3. The composite membrane according to claim 1 or 2, characterized in that The molecular structure of the thermosensitive polymer particles contains amino groups; Preferably, the temperature-sensitive polymer particles include at least one of poly(N,N-dimethylaminoethyl methacrylate), poly((N,N-diethylaminoethyl methacrylate)), and derivatives thereof; Preferably, the average particle size of the temperature-sensitive polymer particles is 200 nm to 300 nm.

4. The composite film according to any one of claims 1 to 3, characterized in that The thickness of the gold nanolayer is 40nm-200nm.

5. The composite film according to any one of claims 1 to 4, characterized in that: The gold nanolayer includes at least one of gold nanoparticles and one-dimensional gold nanomaterials; Preferably, the gold nanoparticles or one-dimensional gold nanomaterials satisfy at least one of the following conditions: a), the average particle size of the gold nanoparticles is 50nm to 150nm; b) the aspect ratio of the one-dimensional gold nanomaterial is 5 to 20; c) The length of the one-dimensional gold nanomaterial is 20nm to 125nm, and the diameter of the one-dimensional gold nanomaterial is 5nm to 25nm.

6. The composite film according to any one of claims 1 to 5, characterized in that: The thickness of the composite film is 0.6 μm to 3 μm.

7. A method for preparing a composite membrane according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: The raw materials of the base film are mixed with the core-shell particles to form a film to obtain the composite film; Preferably, the mass ratio of the raw material of the base film to the core-shell particles is (4-10):

1.

8. The preparation method according to claim 7, characterized in that: The preparation method of the core-shell particles comprises: Mixing the thermosensitive polymer particles, the gold nanolayer material and a solvent, and drying to obtain the core-shell particles; Preferably, the mixing temperature of the thermosensitive polymer particles, the material of the gold nanolayer and the solvent is greater than the critical phase transition temperature of the thermosensitive polymer particles; Preferably, the mixing time of the thermosensitive polymer particles, the material of the gold nanolayer and the solvent is 0.5 h to 2 h.

9. The preparation method according to claim 7 or 8, characterized in that: The mixing temperature of the raw materials of the base film and the core-shell particles is lower than the critical phase transition temperature of the thermosensitive polymer particles.

10. Use of the composite film according to any one of claims 1 to 6 in a cling film or a total heat exchange membrane.